Comparing Strengths and Weaknesses of Learning Theories - Mehri Doosti Irani; Shahla Abolhasani; Fariba Haghani (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Medical education is changing. Therefore, teachers need to evaluate their performance and try to maximize learning. Learning theories can provide insight in this important issue. This study aimed to review the strengths and weaknesses of learning theories including behavioral, cognitive and humanistic theories. Methods: In this study, some literatures related to learning theories including books and articles were selected. Then the selected texts were examined in terms of strengths and weaknesses of learning theories. Results: Results showed that behavioral theories are simple, and easy to use. Learner focused on a clear goal. Cognitive learning theories such as information processing, Gestalt and constructive theories promote critical thinking and problem solving. Therefore, learner can face better to real life. In humanistic learning theory, learner focuses to learn his or her own required things, which their ultimate need is self-actualization. Self-learning is one of the most famous educational principle in this approach which is led to self-direction. Conclusion: Each theory deals with one aspect of learning. Thus, each one has the specific strengths and weaknesses. Instructors and educational planners need to consider these cases for its best application.